Microwave hyperthermia study in breast cancer treatment (2020)
Hyperthermia is the oldest non-surgical technique used in the breast cancer treatment. Hyperthermia is implemented by using ultrasound, nanoparticles, laser and microwave. In this study, the initial effects obtained in the breast cancer treatment by using microwave hyperthermia (EM) are presented. The power density distribution on a breast model affected by a tumor was analyzed. Breast and tumor model were implemented by using the electrical properties of the breast and tumor tissues. The power density distribution was analyzed in 4 different tumor positions inside breast model. The breast model affected by a tumor was irradiated with two applicators at 2.45 GHz. The second applicator, it is a new prototype of applicator developed in the Groove Gap Waveguide technology (GGW). The power density in the breast tissues (fat and lobes) and the tumor is compared. The preliminary results indicate that with the new prototype of applicator developed in the Groove Gap Waveguide technology (GGW) is possible to focus the EM energy. Moreover, the tissues close to the tumor obtain a lower concentration of power density.